Soil erosion study of the gobi desert region using the cesium-137 isotope method : (A case study of the Orog lake are) (Mongolian Journal of Geography and Geoecology, 2022)
This case study of the Orog Lake area in southwest Mongolia aimed to identify the gobi desert soil erosion and redistribution rate using radioactive Cesium-137 isotope and was carried out in 2017. In total, 67 soil samples were collected from 15 cm depth using the core sampling method and analyzed in the laboratory for soil chemical properties and Cesium-137 isotope. For the identification of the soil erosion and redistribution rate, Profile Distribution Model was used. The study area was dominated by Gobi Brown soils with an average SOM value of 0.89%, pH value of 7.9, and calcium carbonate of 4.4 %. The average soil erosion rate of the Orog lake area was 12.57 t ha-1 y -1 . The maximum soil erosion was -40.87 t ha-1 y -1 at the north slopes of Ikh Bogd mountain and the highest soil accumulation rate (7.55 t ha-1 y -1 ) was found in the Solonchak soils in the meadow shoreline of the Orog lake. The soil erosion near the soum settlement area was 30.9 % higher than in the other areas and it was probably due to the impact of human activity and overgrazing. The soil erosion at the northwest windward side of the Orog lake was 14.0 t ha-1 y -1 , which was 38.7 % higher than the east wind leeward side. Besides global warming has negatively impacted soil erosion, livestock number, which has increased 3.2 times within the last 30 years (1987-2017), has become the major factor impacting soil erosion. Therefore, it is important to promote soil conservation activities and to reduce livestock numbers near the soum center to minimize the soil erosion of the Gobi region.Говийн бүсийн хөрсний эвдрэлийг Цези-137 изотоп ашиглан судалсан дүн (Орог нуур  орчмын жишээн дээр)ХУРААНГУЙГовийн бүс нутгийн хөрсний эвдрэл, элэгдэл хуримтлалын зэргийг цацраг идэвхт Цези-137 изотопин арга ашиглан тодорхойлох зорилгоор Монгол орны баруун-урд хэсэг Орог нуур орчим нутгийн жишээн дээр судалгааг 2017 онд хийлээ. Судалгаа явуулсан нутгаас нийт 67 ш. хөрсний дээжийг 15 см-ын гүнээс "Core" аргаар авч, лабораторид хөрсний ерөнхий үзүүлэлтүүд болон Цези-137 изотопыг тодорхойлсон. Хөрсний элэгдэл, хуримтлалын зэргийг тооцоолоход Profile Distribution Model загвар ашиглалаа. Орог нуур орчим говийн бор хөрс зонхилон тархаж хөрсний органик бодис дунджаар 0.89 %, урвалын орчин (рН) 7.9, карбонат 4.4 % байна. Судалгаагаар говийн хөрснөөс жилд 1 га газраас дунджаар 12.57 (т га-1 ж -1 ) тонн хөрс эвдрэлд орж алдагдаж байгааг тогтоов. Их Богд уулын ар хажууд хөрсний хамгийн их эвдрэл -40.78 т га-1 ж -1 хүрсэн бол Орог нуурын эрэг орчмын нугархаг газрын Хужирлаг хөрсөнд хамгийн их хуримтлалтай (7.55 т га-1 ж -1 ) байна. Сумын төв орчмын хөрсний эвдрэл нь бусад харьцуулж буй газраас 30.9 % илүү байгаа нь хүн, мал, машин зэрэг хүчин зүйлстэй холбон тайлбарлах үндэслэлтэй. Орог нуурын баруун-хойд салхин талын хөрсний эвдрэл дунджаар 14.0 т га-1 ж -1 буюу нуурын зүүн хэсгийн хөрснөөс 38.7 % илүү байна. Хөрсний эвдрэлд уур амьсгалын дулаарал сөрөг нөлөө үзүүлэхээс гадна малын тоо толгой 30 жил(1987-2017) 3.2 дахин өссөн нь хөрс эвдрэлд оруулах гол хүчин зүйл болж байна. Говийн бүсийн хөрсний эвдрэлийг багасгахад сумын төв орчмын хөрс хамгаалах үйл ажиллагааг идэвхжүүлж малын тоо толгойг бууруулах бодлого баримтлах шаардлагатай.Түлхүүр үгс: Говь, Монгол, Цези-137, Хөрс, Хөрсний эвдрэл